2016
DOI: 10.3390/genes8010006
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA Profiles in Tobacco- and Alcohol-Associated Diseases

Abstract: Tobacco and alcohol are the leading environmental risk factors in the development of human diseases, such as cancer, cardiovascular disease, and liver injury. Despite the copious amount of research on this topic, by 2030, 8.3 million deaths are projected to occur worldwide due to tobacco use. The expression of noncoding RNAs, primarily microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), is modulated by tobacco and alcohol consumption. Drinking alcohol and smoking cigarettes can modulate the expression of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 115 publications
(206 reference statements)
0
27
0
Order By: Relevance
“…Therefore, the possibility of cancer should also be taken in to consideration in the diagnosis of diabetic nephropathy using lncRNA CASC2 as a marker. Although lncRNAs have been widely used in the diagnosis of various types of human diseases, expression of lncRNAs are affected by many factors such as aging [18], tobacco and alcohol consumption [19], which in turn affects the accuracy of the use of lncRNAs in diagnosis of certain diseases. In this study, serum levels of lncR-NA CASC2 showed no significant correlations with patients' age, gender as well as living habit including smoking and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the possibility of cancer should also be taken in to consideration in the diagnosis of diabetic nephropathy using lncRNA CASC2 as a marker. Although lncRNAs have been widely used in the diagnosis of various types of human diseases, expression of lncRNAs are affected by many factors such as aging [18], tobacco and alcohol consumption [19], which in turn affects the accuracy of the use of lncRNAs in diagnosis of certain diseases. In this study, serum levels of lncR-NA CASC2 showed no significant correlations with patients' age, gender as well as living habit including smoking and drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the relationship between lncRNAs and tobacco use are still preliminary and mainly come from studies addressing human bronchial epithelial (HBE) cells. The two most extensively studied lncRNAs in lung cancer in regard to tobacco use are HOTAIR and MALAT1, which were shown to be upregulated in smokers (Soares do Amaral, Cruz e Melo, de Melo Maia, & Malagoli Rocha, ), but risk factor data from OSCC/TSCC cohorts are sparse. One study using RNASeq analysis identified lncRNAs potentially related to alcohol‐associated HNSCC, but the study did not stratify patients according to anatomical subsite and these finding may not necessarily apply to OSCC alone (Yu et al., ).…”
Section: De Lncrnas and Clinicopathological Featuresmentioning
confidence: 99%
“…Another point of interest is to understand the mechanisms by which the expression of ANRIL is increased in poor prognosis tumors. External risk factors, including lifestyle, nutrition or environment, have been shown to influence the expression of lncRNA 51 . Thus, HOTAIR and MALAT1 have been the most studied lncRNA in the context of tobacco use in lung cancer 51 .…”
mentioning
confidence: 99%